Family history of substance use disorder and parental impulsivity are differentially associated with neural responses during risky decision-making - Aloi, Joseph; Kwon, Elizabeth; Hummer, Tom A.; Crum, Kathleen I.; Shah, Nikhil; Pratt, Lauren; Aalsma, Matthew C.; Finn, Peter; Nurnberger, John; Hulvershorn, Leslie A. (Frontiers in Neuroimaging, 2023)
Background Risky decision-making is associated with the development of substance use behaviors during adolescence. Although prior work has investigated risky decision-making in adolescents at familial high risk for developing substance use disorders (SUDs), little research has controlled for the presence of co-morbid externalizing disorders (EDs). Additionally, few studies have investigated the role of parental impulsivity in offspring neurobiology associated with risky decision-making. Methods One-hundred twenty-five children (28 healthy controls, 47 psychiatric controls with EDs without a familial history of SUD, and 50 high-risk children with co-morbid EDs with a familial history of SUD) participated in the Balloon Analog Risk Task while undergoing functional magnetic resonance imaging. Impulsivity for parents and children was measured using the UPPS-P Impulsive Behavior Scale. Results We found that individuals in the psychiatric control group showed greater activation, as chances of balloon explosion increased, while making choices, relative to the healthy control and high-risk groups in the rostral anterior cingulate cortex (rACC) and lateral orbitofrontal cortex (lOFC). We also found a positive association between greater activation and parental impulsivity in these regions. However, within rACC, this relationship was moderated by group, such that there was a positive relationship between activation and parental impulsivity in the HC group, but an inverse relationship in the HR group. Conclusions These findings suggest that there are key differences in the neurobiology underlying risky decision-making in individuals with EDs with and without a familial history of SUD. The current findings build on existing models of neurobiological factors influencing addiction risk by integrating parental factors. This work paves the way for more precise risk models in which to test preventive interventions.